2009
DOI: 10.1111/j.1365-2842.2008.01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory function in subacute TMD patients before and after treatment

Abstract: Masticatory function can be impaired in temporomandibular disorders (TMDs) patients. We investigated whether treatment of subacute non-specific TMD patients may influence oral function and clinical outcome measures. Fifteen patients with subacute TMD participated in the study. We quantified masticatory performance, maximum voluntary bite force, muscle activity and chewing cycle duration before and after treatment. Masticatory performance and bite force of patients were compared with the results obtained for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 33 publications
5
32
0
7
Order By: Relevance
“…This model have been used in previous studies Bani & Bergamini, 2001;Nogueira-Filho et al, 2004) resulting different degrees of morphologic and physiologic alterations on masticatory muscles, specially masseter. It is important to state that malocclusion may influence the functional performance of the masticatory muscles, resulting on muscular overwork and fatigue (Glaros et al, 2007;Pereira et al, 2009;Van Selms et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…This model have been used in previous studies Bani & Bergamini, 2001;Nogueira-Filho et al, 2004) resulting different degrees of morphologic and physiologic alterations on masticatory muscles, specially masseter. It is important to state that malocclusion may influence the functional performance of the masticatory muscles, resulting on muscular overwork and fatigue (Glaros et al, 2007;Pereira et al, 2009;Van Selms et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors reported correlation between TMD and MBF, when analyzed in individuals with signs and symptoms of this dysfunction and with absence of occlusal problems (23,24) . Conversely, other authors did not observe significant difference between the group with TMD and the group without dysfunction, in relation to MBF.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of muscle pain during mastication, muscle pain or on the TMJ and/or inflammation on the TMJ may influence the reduction of the maximum bite force of individuals with TMD (24) . Thus, evaluation of the bite force is relevant for the diagnosis and treatment planning, since the reduction in force is an important factor on the overload and hyperactivity of masticatory muscles and a common characteristic in individuals with TMD (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Deste modo, em indivíduos com má oclusão a redução da força de mordida máxima está, provavelmente, mais relacionada ao efeito do contato oclusal e da biomecânica dos ossos maxilares e músculos da mastigação do que com a classificação morfológica (BAKKE, 2006 (TATE et al, 1994;IWASE et al, 1998IWASE et al, , 2006 (TATE et al, 1994;ZARRINKELK et al, 1996;IWASE et al, 1998;HARADA et al, 2000;VAN DEN BRABER et al, 2004;IWASE et al, 2006;VAN DEN BRABER et al, 2006;NAKATA et al, 2007), bem como predomínio de sinais e sintomas de DTM em indivíduos com DDF quando comparados a um grupo controle (FARELLA et al, 2007;PAHKALA;KELLOKOSKI, 2007;ABRAHAMSSON et al, 2009;OLAND;JENSEN;MELSEN, 2010). Porém, a relação entre a FMIM e a DTM não foi estudada na literatura, sendo que alguns autores relataram existir uma correlação entre a DTM e a FMIM, quando realizada avaliação em indivíduos com sinais e sintomas desta disfunção e com ausência de problemas oclusais (BONJARDIM et al, 2005;KOGAWA et al, 2006;PIZOLATO et al, 2007;PEREIRA et al, 2009 Atualmente é aceito que o contato prematuro ou as interferências oclusais podem reduzir ou inibir a atividade da musculatura mastigatória, possivelmente para evitar danos às estruturas dento-alveolares devido à interferência oclusal (SAIFUDDIN et al, 2003). Dessa forma, quando há presença de algum fator que altera essa condição normal, como a DTM e a DDF, pode haver um comportamento diferente da musculatura, como foi encontrado nesse estudo durante a análise dos valores numéricos da atividade eletromiográfica, havendo um predomínio da atividade para o músculo temporal anterior em relação ao músculo masseter, durante a prova de CVIM.…”
Section: Discussionunclassified
“…Diferentemente dos resultados do presente estudo, a literatura demonstra redução significante da atividade eletromiográfica de indivíduos com DDF, em tratamento ortodôntico pré-cirúrgico, quando comparados ao grupo controle com oclusão normal e ausente de sinais e sintomas de DTM (TATE et al, 1994;ZARRINKELK et al, 1996; VAN DEN BRABER et al, 2004;TRAWITZKI et al, 2006;NAKATA et al, 2007;SFORZA et al, 2008;TRAWITZKI et al, 2010 VISSER et al, 1994;TOSATO;CARIA, 2007;TARTAGLIA et al, 2008;PEREIRA et al, 2009;ARDIZONE et al, 2010 (FERRARIO et al, 2000). Além disso, a assimetria da atividade da musculatura mastigatória aumenta com a contração muscular, diminuindo os níveis e o valor da assimetria, sendo sempre maior no músculo masseter do que no músculo temporal (SAIFUDDIN et al, 2003).…”
Section: Discussionunclassified